Islamic Banks and Profitability: An Empirical Analysis of Indonesian Banking - Jordan, Sarah (2013)
This paper provides an empirical analysis of the factors that determine the profitability of Indonesian banks between the years 2006-2012. In particular, it investigates whether there are any significant differences in terms of profitability between Islamic banks and commercial banks. The results, obtained by applying the system-GMM estimator to the panel of 54 banks, indicate that the high bank profitability during these years were determined mainly by the size of the banks, the market share as measured by the industry concentration index and the interest rate levels. In addition, we find that the financial structure as measured by the customer deposits to the total liabilities ratio and the annual customer deposits growth rate do not affect banks’ profitability. On the other hand, the macroeconomic determinants such as GDP and inflation, with the exception of interest rate, have no influence on bank profitability. Finally, our study reveals that there are no significant differences in the profitability of Islamic and commercial banks. These findings apply only when using return on assets (ROA)as the profitability measure. Key words: Banks’ Profitability  Commercial Banks  Indonesia Islamic Banks